PERSEPSI PETANI TENTANG PERAN PENYULUH PERTANIAN DALAM PENINGKATAN PENDAPATAN PETANI JAGUNG HIBRIDA - Novianda Fawaz Khairunnisa; Zumi Saidah; Hepi Hapsari; Eliana Wulandari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Agricultural extension agents have a strategic role in helping farmers to increase their farming. The role of agricultural extension agents includes fostering farmers in managing their farms effectively and efficiently so that they can increase farmers' income. Nunuk Baru Village is one of the corn commodity development areas that has received more attention in agricultural extension activities because of its potential productivity and planting area for corn. This study aims to identify the role of agricultural instructors for maize farmers and to analyze the influence of the role of agricultural instructors on the income level of maize farmers. The research design used is a quantitative approach with a survey method. The respondents of this research were 80 corn farmers. Methods of data analysis in this study using descriptive analysis using a sematic differential scale and multiple linear regression analysis. The results of this study indicate that the role of agricultural extension agents in Nunuk Baru Village, Maja District, Majalengka Regency is categorized as very good in their role as a catalyst, communicator, consultant and organizer while as a motivator, educator and facilitator are categorized as good. The role of agricultural extension agents has no significant effect on the income of maize farmers in Nunuk Baru Village.